Does social integration matter for cohort differences in the political participation of internal migrants in China?. Issue 3 (16th March 2022) - Lu, Haiyang; Kandilov, Ivan T.; Zhu, Rong
Abstract: Using nationally representative data from the 2017 National Internal Migrants Dynamic Monitoring Survey, this paper examines the nexus between social integration and the political participation of internal migrants in China. We document a positive association between social integration status and internal migrants' political participation. The study further examines the political participation differentials from two perspectives: between migration types and between migration distances. Our Oaxaca–Blinder decomposition analysis suggests that while only about 5.2% of the political participation differential between urban‐to‐urban migrants and rural‐to‐urban migrants is attributable to the difference in social integration status, the difference in social integration status explains about 12.0% of the participation gap between intra‐provincial migrants and inter‐provincial migrants. Our findings suggest that regionally diverse social integration policies may have unintended consequences for the political participation of migrant workers in China.